Onset and nonlinear regimes of convection of ternary mixture in a rectangular porous cavity taking into account Soret effect - Lyubimova, Tat’yana Petrovna; Zubova, Nadezhda Alekseyevna (Computational Continuum Mechanics, 2019)
A numerical study has been conducted to investigate the onset and nonlinear regimes of Soret-induced convection of a mixture of dodecane, isobutylbenzene and tetralin at equal mass fraction proportions in a rectangular porous cavity with solid boundaries elongated in a horizontal direction and heated from below. The vertical boundaries of the cavity are insulated. The components of the mixture are representatives of the main groups of chemical compounds that make up the oil. The values of porosity and permeability of the medium were chosen close to the values of real media, such as sands, sandstones or limestone. The area of such configuration simulates a real hydrocarbon field. Due to the Soret effect, the light components of the mixture, dodecane and isobutylbenzene, which have positive separation ratios, accumulate in the hot region, and the heavy component of the mixture, tetralin, in the cold region. This leads to the onset of convection in the case of heating from below, which in natural conditions is ensured by the presence of a geothermal gradient. It has been found that at a certain value of the Rayleigh number a steady flow occurs in the cavity, which, with an increase in the Rayleigh number, is replaced by an oscillatory one. With a further increase in the Rayleigh number, irregular oscillations occur. In the considered interval of the Rayleigh numbers, several monotonic and oscillatory regimes characterized by different spatial scales (from one to ten vortexes) were found. The form of oscillations of instantaneous flow characteristics in oscillatory regimes has a complex shape. The monotonic flow regime with an asymmetric structure was revealed. The intervals of the Rayleigh numbers, in which the obtained regimes may exist, and the time dependences of the integral characteristics occurred in the process of formation of steady flows were determined. The effect of supercriticality on the flow structure and the concentration distribution of mixture components were studied.
Keywords: convection; diffusion; Soret effect; ternary mixture; porous medium